1037. Qualitative Findings from a Hybrid III Implementation-Effectiveness Study to Explore Perspectives of Health-care Staff on Early Implementation of Cabotegravir and Rilpivirine Long Acting (CAB+RPV LA) Injectable HIV treatment in the US (CUSTOMIZE). (31st December 2020) - Czarnogorski, Maggie; Garris, Cindy; Wannamaker, Paul; D'Amico, Ronald; Selenski, Carolyn; Williams, Will; McHorney, Colleen A; Stassek, Larissa; Wohlfeiler, Michael; Sinclair, Gary I; Mena, Leandro A; Margolis, David
Abstract: Background: CAB+RPV LA administered monthly for HIV treatment is non-inferior to daily oral ART at maintaining HIV suppression but concerns about implementation of this novel treatment paradigm remain. CUSTOMIZE, an implementation-effectiveness study, examined barriers and facilitators to successful implementation of CAB+RPV LA in US HIV clinics. Methods: Semi-structured qualitative interviews were conducted with physicians, injectors, and administrators across diverse clinics in US without previous CAB+RPV LA experience at Baseline (BL) (N=26) and after patients received the 4 th monthly injection of CAB + RPV LA (interim) (N=24). Consolidated Framework for Implementation Research (CFIR) guided the interviews to evaluate barriers and facilitators to implementation. Interviews were recorded, transcribed, and coded using ATLAS.ti then analyzed for trends. Results: At BL, 58% of study staff expected CAB+RPV LA would meet the needs of patients. Staff reported perceived advantages for patients: reduced stigma of pill bottles (38%), ability to live/travel in a "carefree" manner (31%) and removing the daily reminder of HIV (20%). At BL, most administrators had resource concerns: additional refrigeration, transportation, and staffing. Some clinics (38%) needed to purchase a refrigerator to store CAB+RPV LA. Some physicians noted a potential need for improved parking or expanded hours. At interim, most staff (71%) reported no change in official clinic hours; but 50% of injectors and 38% of administrators reported changing work hours to accommodate injection visits before clinic or at lunchtime. Existing appointment reminder systems and transportation support were reported as facilitators to implementation. Many staff (46%) noted additional visits increased coordination of other care needs. Most staff (67%) noted high patient acceptance and positive attitudes facilitated successful implementation of CAB + RPV LA. Conclusion: Some staff had concerns about implementation initially, but at study interim minimal practice changes were needed to operationalize CAB+RPV LA effectively. Patient interest heightened staff desire to implement CAB+RPV LA in their clinics. Staff are optimistic that monthly CAB+RPV LA is manageable with minimal disruption to routine care in US HIV care settings. Disclosures: Maggie Czarnogorski, MD, MPH, ViiV Healthcare (Employee) Cindy Garris, MSPH, GlaxoSmithKline (Other Financial or Material Support, Stockholder)ViiV Healthcare (Employee) Paul Wannamaker, BA, ViiV Healthcare (Employee) Ronald D'Amico, DO, MSc, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Carolyn Selenski, PhD, GSK (Employee, Shareholder) Colleen A. McHorney, PhD, Evidera (Employee) Larissa Stassek, MPH, Evidera (Employee) Gary I. Sinclair, MD, ViiV (Speaker's Bureau) Leandro A. Mena, MD, MPH, Binx Health (Grant/Research Support)Evofem (Grant/Research Support)Gilead Science (Consultant, Grant/Research Support, Speaker's Bureau)GSK (Grant/Research Support)Janssen (Grant/Research Support)Merck (Consultant, Grant/Research Support)Roche Molecular (Consultant, Grant/Research Support)SpeedDx (Grant/Research Support)ViiV Healthcare (Consultant, Grant/Research Support, Speaker's Bureau) David Margolis, MD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee)